Counterpropaganda researches in Ukrainian soviet periodicals based on the materials of the special fonds of the Central Scientific Library of the Academy of Sciences of the Ukrainian SSR - Dzyra Olesia (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the work is to analyze and systematize the articles of Soviet scientists who were readers of the special fonds of the Central Scientific Library of the Academy of Sciences of the Ukrainian SSR and published articles, based on its materials in the bulletin of the Institute of History "Foreign Publications about Ukraine". Methodology. The methods of analysis and synthesis, induction and deduction were used in the preparation of the article; historical and comparative - to compare the assessments of state-building processes in Ukraine by diaspora scientists and Soviet ones; historiographical analysis - to study the publications of contributors to the aforementioned bulletin. The scientific novelty of the worklies in the familiarization and characteristics of little researched counterpropaganda publications on the pages of the journal of the department of foreign historiography of the Institute of History of the Academy of Sciences of the Ukrainian SSR. Conclusions. Since the end of the 1960s, the special storage fonds of the Vernadsky National Library of Ukraine became the main repository of foreign Ukrainica literature and forbidden publications in the USSR, which became a source for counterpropaganda researches at the Institute of History of the Academy of Sciences of the Ukrainian SSR. They were accomplished by the department of foreign historiography, which was specially created in those years, which was also involvedin the direct book acquisition of the special fonds by ordering publications necessary for investigations of their staff members. The results of these studies were publishedin the journal "Foreign publications about Ukraine: scientific and abstract bulletin", which was published four times a year and was intended for official use. The authors of the articles proved the "falsification" character of the scientific works of diaspora scientists aimed at destabilizing the political situation in the USSR. They depicted the Soviet reality and history according to the pattern determined by the Communist Party in order to preserve the established totalitarian regime.